Providing informal care in a changing society - Broese van Groenou, Marjolein I. (Eur J Ageing, 2016)
The ageing of society is leading to significant reforms in long-term care policy and systems in many European countries. The cutbacks in professional care are increasing demand for informal care considerably, from both kin and non-kin. At the same time, demographic and societal developments such as changing family structures and later retirement may limit the supply of informal care. This raises the question as to whether the volume of informal care (in people) will increase in the years ahead. This paper aims to provide a theoretical answer to this question in two steps. First, based on different care models and empirical literature, we develop a behavioural model on individual caregiving, the Informal Care Model. The model states that, in response to the care recipient’s need for care, the intention to provide care is based on general attitudes, quality of the relationship, normative beliefs, and perceived barriers. Whether one actually provides care also depends on the care potential of the social context, being the family, the social network, and the community. Second, we discuss how current policy and societal developments may negatively or positively impact on these mechanisms underlying the provision of informal care. Given the increased need for care among home-dwelling individuals, the model suggests that more people will take up the caregiver role in the years ahead contributing to larger and more diverse care networks. It is concluded that long-term informal care provision is a complex phenomenon including multiple actors in various contexts. More research is needed to test the Informal Care Model empirically, preferably using information on care recipients, informal caregivers and community care in a dynamic design and in different countries. Such information will increase insight in the developments in informal care provision in retrenching welfare states.